On the capacity to suffer one's self - Mizen, Richard (Journal of analytical psychology, 2014)
Problems in the establishment of the sense of a ‘psychic’ skin, in the ways described by Bick and Meltzer for example, commonly give rise to distortions in the capacity for self-experiences as a consequence of difficulties in relation to projective and identificatory processes. These latter may acquire a markedly adhesive character as a defence against the anxieties that arise. This makes for considerable technical difficulties in an analysis. This essay addresses the nature of these problems and considers some of the ways in which they may be approached clinically.